Impact of Outsourcing on Organizational Productivity in Private and Public Sector Organizations in Anambra State - Okeke-Ezeanyanwu, Joy. A. (African Journal of Education,Science and Technology (AJEST), 2017)
The study focused on the impact of outsourcing on organizational productivity in public and private sector organization in Anambra state. Literature related to outsourcing were reviewed and there was no evidence of significant research. On the impact of outsourcing on organization' productivity. Two research questions and one null hypothesis were formulated for the study. The population of the study consisted of manager of all public and private organizations engaged in outsourcing in Anambra state. Stratified random sampling was adopted and a sample size of 310 managers was used for the study. Questionnaire was used as the instrument for data collection. Frequency count and percentages was used to analyze data relating to research questions while Chi-Square (X2) statistical tool was used to test the hypotheses. The results of the data analyzed showed that outsourcing has positive as well as negative impact on organization in both sectors. It was concluded that for managers of organizations to achieve successful outsourcing of their activities, there is need to increase the positive effects while reducing the negative effects and to adopt outsourcing framework which is strategically sound for proper formulation of outsourcing decisions.'